MANAGEMENT OF LARGE IDIOPATHIC MACULAR HOLE WITH PARS PLANA VITRECTOMY AND MODIFIED MINIMAL ILM PEELING WITH SUPERIOR ILM FLAP - Fatimah Syakirah; Ramzi Amin; Abdul Karim Ansyori (International Journal of Retina, 2022)
Introduction: Idiopathic macular hole is an anatomic discontinuity of the neurosensory retina in the center of the macula or fovea resulted from tractional forces on the foveola at the vitreoretinal interface not associated with other causes. Diagnosis and management of this condition requires expertise, skills, and specialized examination to detect changes in the retina which is important for deciding the appropriate management. Case Report: We report a case of 66-year-old man with idiopathic macular hole (IMH) in the right eye with initial best corrected visual acuity (BCVA) 20/1200. Fundus examination and optical coherence tomography (OCT) confirmed the presence of large full thickness macular hole with mean linear diameter 673 µm and posterior hyaloid still attached to the optic nerve. The patient was managed with pars plana vitrectomy (PPV) surgery using modified minimal internal limiting membrane (ILM) peeling with superior ILM flap and SF6 gas tamponade. Two weeks after surgery OCT showed closure of the macular hole. BCVA at two and four weeks after surgery improved to 20/240 and 20/200 respectively. Discussion: PPV with ILM peeling is one of the standardized procedures in IMH surgery. Failure of the vitrectomy surgery to close the macular hole or late reopening of initially successfully closed holes may occur without removal of the ILM due to ILM role as a scaffold for cellular proliferation or attachment of contractile tissue that may cause persistent vitreomacular traction. Variations of ILM peeling such as inverted ILM peeling has been used to improve closure rate for large IMH and has showed favorable results both anatomically and functionally. Nowadays, to avoid or minimize the damage of retinal microstructure by ILM peeling, some surgeons introduced new techniques aiming to preserve the ILM for IMH. Minimal ILM peeling with superior ILM flap technique in this case was done to obtain MH closure with less microstructural retinal abnormalities and better visual outcomes. Conclusion The management of large IMH with PPV and modified minimal ILM peeling with superior ILM flap in this case showed good results in terms of anatomic and functional outcomes.